The role of Community-Based Disaster Preparedness and Response Team in building community resilience - Erni Suharini; Siti Asiah; Kurniawan, Edi (Penerbit Universiti Kebangsaan Malaysia, 2020)
The community and government of Kalipancur Village have realised and implemented the landslide disaster mitigation efforts known as Community-Based Disaster Preparedness and Response Team (SIBAT Team) as a part of the Disaster Risk Reduction Forums (FPRB) in Kalipancur Village. The purpose of this study was to determine the role of the SIBAT Team in implementing the resilience of the community of Kalipancur, especially the residents of RW 1, who live in landslide-prone areas. The sample in this study consisted of the SIBAT Team and residence of Kalipancur Village from RW I that were chosen using proportional random sampling. Data collection techniques used were observation, tests, questionnaires, and interviews. The data analysis techniques used consisted of qualitative data analysis technique with interactive methods and quantitative data analysis with descriptive analysis technique. The results showed that the SIBAT Team has a big role in building community resilience in Kalipancur Village in disaster mitigation education and emergency response efforts. The magnitude of the role of the SIBAT Team is directly proportional to the high level of community resilience in all aspects of the Kalipancur community. This research exemplifies that the Community-Based Disaster Risk Reduction (CBDRR) program is a strategic effort in building community resilience. Therefore, the sustainability of the CBDRR program is a necessity, and collaboration between the government, NGOs, and communities that combines bottom-up and top-down approaches will be an effective effort to build community resilience.